The Impact of Recent Alcohol Use on Genome Wide DNA Methylation Signatures - Philibert, Robert; Plume, Jeffrey M.; Gibbons, Frederick X.; Brody, Gene H.; Beach, Steven (Frontiers in Genetics, 2012)
Chronic alcohol intake is associated with a wide variety of adverse health outcomes including depression, diabetes and heart disease. Unfortunately, the molecular mechanisms through which these effects are conveyed are not clearly understood. To examine the potential role of epigenetic factors in this process, we examined the relationship of recent alcohol intake to genome wide methylation patterns using the Illumina 450 Methylation Bead Chip and lymphoblast DNA derived from 165 female subjects participating in the Iowa Adoption Studies. We found that the pattern of alcohol use over the 6 months immediately prior to phlebotomy was associated with stepwise, severity -dependent changes in the degree of genome wide methylation that preferentially hypermethylate the central portion of CpG islands with methylation at cg05600126, a probe in ABR, attaining genome wide significance. Gene pathway analysis of nominally significantly differentiated probes demonstrated that chronic alcohol use has profound effects on a diverse cadre of cellular metabolic pathways. We conclude that recent alcohol use is associated with widespread changes in DNA methylation in women and that further study to confirm these findings and determine their relationship to somatic function are in order.